Introducing green investments into Colombia’s works-for-taxes mechanism: A peacebuilding project in Belén de los Andaquíes - Castro Nunez, Augusto Carlos; Borda Almanza, Carlos Andrés; Amahnui, George Amenchwi; Vanegas Cubillos, Martha Cristina (2024)
The Bioversity-CIAT Alliance helped integrate green business projects into Colombia’s Works-for-Taxes mechanism, enabling investments in low-emission food systems through cocoa agroforestry in conflict-affected Belén de los Andaquíes. This model allows companies to offset taxes by investing in sustainable projects that replace illicit economies and restore land. The pilot’s success paves the way for expanding similar initiatives, increasing funding for low-emissions development in Colombian regions impacted by deforestation and conflict.